Assessment of Knowledge, Attitudes, and Practice on Contraceptive Use among Women Attending Family Planning Services in Some Health Centers of Muhima District Hospital, Rwanda - Frederic, Tegera Mpamya; Phoibe, Kanyange; Ntaganira, Joseph (Open Science Journal, 2017)
Introduction: In developing countries, especially in Africa, reproductive health is a great concern to many stakeholders as maternal mortality and morbidity are very high compared to that in the developed world. Moreover, reproductive health knowledge and access to quality maternal health services in Africa are poor with significant health consequences. Appropriate reproductive health knowledge and attitude can empower women to access quality family planning services (preventive and curative), which are essential for improvement of women’s reproductive health. Objectives: This research aimed to assess reproductive health knowledge, attitude, and practice on contraceptive use among women attending family planning services at Muhima district hospital. Methods and Materials: The study was cross-sectional in nature involving 326 randomly selected respondents among women attending family planning services at Muhima district hospital. The study instrument was a self-administered questionnaire. Data was analyzed using SPSS (Statistical Package for Social Science) statistics software 17.0 version. Hypothesis: Looking at the aforementioned objective, one may wonder if the health education on contraceptive use given by health staff of Muhima district hospital is well done; we may also wonder about reproductive health beliefs and determinants of contraceptive use among women attending the family planning service; and to what extent women in Muhima district hospital have access to health education on contraceptive use. Trying to find an interim response to this question, we have come to realize that the impact of belief in personal and community health practices is strong; but individual beliefs may not be scientifically true and as such, may make one rightly or wrongly access health care. Results: The majority of the respondents knew when pregnancy can occur and believed that having sex even once with a man may result in pregnancy. 90.0% of respondents had knowledge of benefits of family planning. Consideration about personal health (86.0%) and husband’s approval (74.9%) were major determinants of respondents’ use of contraceptives. Conclusions: Though respondents were knowledgeable about the benefits of family planning, there is the need for continuous education of women about reproductive health issues and integration of men’s participation in the family planning program to increase utilization of family planning services at Muhima district hospital.